Nursing interventions in patients after lung biopsy - Tomić, Uroš (Education and Research in Health Sciences, 2023)
Introduction: Lung biopsy is a relatively frequent multidisciplinary procedure that is accompanied by a certain percentage of morbidity and mortality. The incidence of complications in a performed lung biopsy depends ona number of factors. In order to prevent and diagnose complications after the biopsy, it is necessary for a patient to be continuously monitored by a nurse.Objective: To consider the importance of nursing interventions in patients after lung biopsy.Respondents and method: The study involved 50 patients, hospitalized at the pulmonology department of the clinic for pulmonology of the Military Medical Academy in Belgrade, who underwent a lung biopsy. A specially created questionnaire for patients consisting of 15 questions was used as an instrument.Results: The largest percentage of surveyed patients is men, aged 50 to 69, who have finished high school and live in the countryside. One-fifth of the subjects had a chest drain inserted after a lung biopsy. The obtained results indicate that in the field of health care, after the lung biopsy, the most important thing is to monitor vital functions, place patients in a certain position and monitor the symptoms and signs of possible complications.Conclusion: Based on the conducted research, we came to the conclusion that nursing interventions in the patient after lung biopsy are of great importance. Adequate patient care results in quicker recovery of the patients and fewer complications.
Keywords: biopsy; lungs; nurse; patient